PENGETAHUAN MASYARAKAT TENTANG MANFAAT VAKSIN COVID – 19 DI DUSUN SUKA MAKMUR KABUPATEN ROKAN HULU - Lora Marlita; saniya saniya; Roza Roza (LPPM Universitas Abdurrab, 2023)
WHO has declared Covid-19 a pandemic. Indonesia is procuring vaccines for the prevention of Covid-19. The purpose of this study was to determine the description of public knowledge about the Covid-19 vaccine in Suka Makmur Hamlet, Rokan Hulu Regency in 2022. This research method was a quantitative study with a descriptive design. This study uses a purposive sampling technique so that the number of samples used is 73 people with the instrument using a multiple choice question questionnaire consisting of 20 questions distributed through coming to people's homes. The results of this study indicate that people's knowledge is in the sufficient category of 34 people (46.6%), having less knowledge 28 people (38.3%), and having good knowledge of 11 people (15.1%). The level of knowledge of the people of Suka Makmur Hamlet, Rokan Hulu Regency about the Covid-19 vaccine, which is sufficient knowledge of 34 people (46.6%). It is hoped that the community will be able to increase public knowledge about the COVID-19 vaccine.